Lexical stress perception : a case study on Tamil-English bilinguals - Lim, Samantha JieYing (2014)
Past research has shown that one’s L1 phonological system influences subsequent perception and learning of a second language, including the domain of stress. Speakers from a non–stress language background often make a considerable number of stress errors when learning an L2 with a stress system. Interestingly, this difficulty has been shown to persist in some cases with bilinguals where one of the native languages contained stress (Doupoux et al., 2010).